Comparison of Whole-Body Electromyostimulation versus Recognized Back-Strengthening Exercise Training on Chronic Nonspecific Low Back Pain: A Randomized Controlled Study - Weissenfels, Anja (Biomed Res Int, 2019)
BACKGROUND: Low back pain (LBP) affects almost everyone at least once in their lifetime. Various meta-analyses show promising effects on pain reduction for conventional exercise. However, the lack of time and, especially for pain patients, a fear of movement (“kinesiophobia”) as well as functional limitations often oppose participation in such activities. In contrast, the advantage of novel training technologies like whole-body electromyostimulation (WB-EMS) lies particularly in a joint-friendly, time-effective, and highly customized training protocol and might be an alternative option for LBP patients. A meta-analysis of individual patient data and a comparison of WB-EMS against a passive control group confirmed the proof principle. Thus, the aim of this randomized controlled trial is to compare WB-EMS with a recognized back-strengthening exercise protocol to determine the corresponding effects on chronic, nonspecific LBP in people suffering from this. METHODS AND FINDINGS: This randomized, controlled multicenter study is focused on novel and time-effective training technologies and LBP. In this contribution, the focus is primarily on the comparison of WB-EMS against a comparable conventional exercise training (CT). One hundred ten nonspecific chronic LBP patients, 40–70 years old, were randomly allocated to the intervention arms (WB-EMS: 55 vs. CT: 55). Both groups completed a 12-week program (WB-EMS: 1 × 20 min/week vs. CT: 1 × 45 min/week) specifically dedicated to LBP. The selection of the content of the active control group was based on the principles of WB-EMS training, which uses electrical stimulation to train mainly strength and stabilization in a very short time. Exercises were similar in all groups, with the focus on strengthening and stabilizing the trunk. Outcome measures were assessed by a four-week pain diary (before and during the last four weeks of intervention) as well as an isometric maximum strength measurement of the trunk muscles at baseline and after 12 weeks of intervention. Primary study endpoint was average pain intensity at the lumbar spine. Secondary study endpoints were maximum isometric strength of the back and the abdominals. The mean pain intensity of LBP decreased significantly in both groups (WB-EMS: −22.3 ± 20.9% vs. CT: −30.2 ± 43.9%; p < 0.001), however, without significant intergroup difference (p=0.160). A similar result was observed for “maximum isometric strength of trunk muscles.” The increase in back strength (WB-EMS: 15.6 ± 24.9% vs. CT: 23.0 ± 30.9%) was highly significant in both groups (p=0.001), and similar changes were observed for the trunk flexors (WB-EMS: 17.6 ± 24.8% vs. CT: 18.1 ± 24.8%). Also, at the secondary endpoint, no significant difference in pairwise comparison was observed in both cases (extension: p=0.297; flexion: p=0.707). CONCLUSION: In summary, both, WB-EMS and conventional back-strengthening protocol are comparably effective in reducing nonspecific chronic LBP in this dedicated cohort. The result is particularly positive in terms of time effectiveness and offers an adequate alternative for people with limited time resources or other barriers to conventional training methods.